Math, asked by aakashtech01, 1 year ago


(x - 1) {}^{4}  - (x - 1) {}^{2 }

Answers

Answered by navya733
0

Answer:

0 is the answer

Step-by-step explanation:

(x+1)-(x+1)

o

Answered by adrija7
2

Step-by-step explanation:

 {(x - 1)}^{4}  -  {(x - 1)}^{2}  \\  =   </em><em>[</em><em>{ {(x - 1)}^{2} }</em><em>]</em><em>^{2}  -  {(x - 1)}^{2}  \\  =  {a}^{2}  -  {b}^{2}  \\  = (a + b)(a - b) \\  = </em><em>[</em><em> {(x - 1)}^{2}  + x - 1</em><em>]</em><em>[</em><em> {(x - 1)}^{2}  - x + 1</em><em>]</em><em>\\  = ( {x}^{2}  - 2x + 1 + x - 1)( {x}^{2} - 2x + 1 - x + 1 ) \\  = ( {x}^{2} - x )( {x}^{2}  - 3x + 2) \\  = ( {x}^{2} - x )({x}^{2}  - 2x - x + 2) \\  = ( {x}^{2} - x )</em><em>[</em><em>x</em><em>(x - 2) - 1(x - 2)</em><em>]</em><em> \\  = ( {x}^{2}  - x)(x - 1)(x - 2)

Similar questions